The Institutional Strategy of the Community Fire Brigade in Control of Forests and Land in Lukun Village, Tebing Tinggi Timur, Meranti Islands Regency - Nur Suhada; Meyla Suhendra; Perijal Chandra Damanik; Dinda Kurnia Shafitri; Khairuniah (Jurnal Ilmu Ilmu Kehutanan, 2022)
This study aimed to identify barriers among fire-aware communities in fulfilling their role in forest and land fire control and to find out the MPA's institutional strategy for forest and land fire control. This study was carried out from November 2019 to December 2019 at Lukun Village, Tebing Tinggi Timur District, Meranti Islands Area with the survey method divided into two activities, the first being group discussion. gather and interview people interested in fire. The obstacles faced by community organizations related to fire are the lack of incentives for the MPA, inadequate equipment for extinguishing fires, limited water resources at the site, transportation and accessibility. At the time of extinguishing the fire was inadequate, no health. and ensure safety when extinguishing fire, when extinguishing. Institutional strategies for forest and land fire control include conducting periodic patrols, educating the community on the use of fire in plantations, and introducing village conventions on peat community activities. in gardens and forests, law enforcement against illegal logging in forested areas, and reserve replacement reservoirs. containment of water and channels to increase moisture and irrigation around potential wildfire risk areas and soil.